2019
DOI: 10.1021/acs.orglett.9b01886
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Synthesis of N-(Carboselenoate) Benzimidazolones by Cascade Cyclization of ortho-Diisocyanoarenes and Selenosulfonates

Abstract: A facile synthesis of N-(carboselenoate) benzimidazolones through metal-free reactions of ortho-diisocyanoarenes with selenosulfonates is reported here. The desired products are obtained in moderate to good yields with good functional group compatibility. The ortho-diisocyanoarenes are applied to the construction of 2-benzimidazolone derivatives for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Then, we screened a range of bases including Na 2 CO 3 , Li 2 CO 3 , Na 2 HPO 4 and DABCO. The results showed that different bases had little influence on this reaction (Table 1, entries [11][12][13][14]. But when no base was added to the reaction, the yield sharply dropped to 31% (Table 1, entry 15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we screened a range of bases including Na 2 CO 3 , Li 2 CO 3 , Na 2 HPO 4 and DABCO. The results showed that different bases had little influence on this reaction (Table 1, entries [11][12][13][14]. But when no base was added to the reaction, the yield sharply dropped to 31% (Table 1, entry 15).…”
Section: Resultsmentioning
confidence: 99%
“…[11] Isonitriles are very good radical acceptors and have been used for the synthesis of a broad variety of nitrogen-containing molecules. [12] Our group has successfully constructed camptothecins, benzothiazoles and cyclopenta[b]quinoxalines through isonitriles involede radical cascade cyclization. [13] Now, we tried to achieve a cascade cyclization of ortho-diisocyanoarenes for the construction of benzo [a]phenazine skeletons by introducing a benzene ring to the radical source.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, isocyanide insertion reactions enable the facile construction of heterocycles . By virtue of the ortho -diisocyanoarenes 157 - 4 as substrates, this radical-chain protocol was further applied to metal-free synthesis of N -(carboselenoate) benzimidazolones 157 - 5 , boosting its practicality (Scheme B) . Heating the reaction at 50 °C and employing t BuOH were found to benefit the reaction efficiency.…”
Section: Radical-mediated Desulfonylation Of Thio/selenosulfonates Vi...mentioning
confidence: 99%
“…Recently, several examples of quinoxaline syntheses from o -diisocyanoarenes via radical-mediated perfluoroalkyliodination , and hydrophosphorylation processes have been reported (Scheme a,b), and the efficient syntheses of N -(carboselenoate)­benzimidazolones via the cascade cyclization reactions of o -diisocyanides have also been reported (Scheme c). These reactions utilize the good radical acceptor properties of isocyanides …”
Section: Introductionmentioning
confidence: 99%